PENGEMBANGAN KETERAMPILAN MEMBACA PUISI DENGAN TEKNIK PERMODELAN PAR (PARTICIPATORY ACTION RESEARCH) PADA SISWA - Farihatul Arofah; Moh. Badiul Anis (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
The purpose of this study is, First, to examine poetry reading skills in third grade students of Madrasah Ibtidaiyah in Kudus district. Secondly, developing poetry reading skills in MI III students in Kudus district. This research uses modeling techniques with PAR approaches and methods. The data obtained from various data collection techniques were analyzed using descriptive analysis. The results of this study showed that the development of modeling techniques was able to improve poetry reading skills in third grade MI students who became research sites. Through the development of this PAR modeling approach students are given examples in advance so that students can develop their poetry reading skills. The teacher's role in this research is as a facilitator as well as a student motivator to read poetry well. From the analysis, there was a finding that students' poetry reading skills improved after the application of modeling techniques in learning Indonesian, especially in poetry reading material. Based on the results of the study, it was concluded that, the development of modeling techniques can improve students' poetry reading skills.Keywords: Development, PAR, Poetry Reading Skills